PERBEDAAN KARAKTERISTIK PASIEN PERITONITIS SEBELUM DAN SELAMA PANDEMI COVID-19 DI RSUD ULIN BANJARMASIN Tinjauan Terhadap Usia, Lama Datang, Jenis Penanganan, dan Penyebab - Fadhilah, Nur; Wibowo, Agung Ary; Noor, Meitria Syahadatina; Lahdimawan, Ardik; Skripsiana, Nika Sterina (Homeostasis, 2023)
Peritonitis is an inflammation that occurs in the peritoneal organs. Coronavirus Disease 2019 (COVID-19) has been declared a pandemic. This study aims to analyze the characteristics of peritonitis patients before and during the COVID-19 pandemic at RSUD Ulin Banjarmasin which were reviewed based on age, length of arrival, type of treatment, and causes. This research is an analytic observational study using a retrospective cohort study design. The subjects of this study were peritonitis patients at RSUD Ulin Banjarmasin from March 2018 – February 2022 who fit the inclusion criteria. The sampling method before the COVID-19 pandemic used simple random sampling and during the COVID-19 pandemic used total sampling. The results showed that the mean age of peritonitis patients before and during the COVID-19 pandemic was 33.75 ± 16.92 and 40.05 ± 19.99 (p=0.185), the average length of arrival was 4.26 ± 4.70 and 3 .40 ± 3.91 (p=0.234), and the Chi-Square test on the variable type of treatment obtained p value =0.320 and the cause obtained p value=0.558. It can be concluded that there is no difference in age, length of arrival, type of treatment, and causes of peritonitis patients before and during the COVID-19 pandemic at RSUD Ulin Banjarmasin.